Graphene-Based Nanomaterials Modulate Internal Biofilm Interactions and Microbial Diversity - Evariste, Lauris; Braylé, Paul; Mouchet, Florence; Silvestre, Jérôme; Gauthier, Laury; Flahaut, Emmanuel; Pinelli, Eric; Barret, Maialen (Frontiers in Microbiology, 2021)
Graphene-based nanomaterials (GBMs) such as graphene oxide (GO) and reduced graphene oxide (rGO) possess unique properties triggering high expectations for the development of new technological applications and are forecasted to be produced at industrial-scale. This raises the question of potential adverse outcomes on living organisms and especially toward microorganisms constituting the basis of the trophic chain in ecosystems. However, investigations on GBMs toxicity were performed on various microorganisms using single species that are helpful to determine toxicity mechanisms but fail to predict the consequences of the observed effects at a larger organization scale. Thus, this study focuses on the ecotoxicological assessment of GO and rGO towards a biofilm composed of the diatom Nitzschia palea associated to a bacterial consortium. After 48 and 144 hours of exposure to these GBMs at 0, 0.1, 1 and 10 mg.L-1, their effects on the diatom physiology, on the structure and the metabolism of bacterial communities were measured through the use of flow cytometry, 16S amplicon sequencing and Biolog ecoplates, respectively. The exposure to both of these GBMs stimulated the diatom growth. Besides, GO exerted strong bacterial growth inhibition as from 1 mg.L-1, influenced the taxonomic composition of diatom-associated bacterial consortium, and increased transiently the bacterial activity related to carbon cycling, with weak toxicity towards the diatom. On the contrary, rGO was shown to exert a weaker toxicity toward the bacterial consortium whereas it influenced more strongly the diatom physiology. When compared to the results from the literature using single species tests, our study suggests that diatoms benefited from diatom-bacteria interactions and that the biofilm was able to maintain or recover its carbon-related metabolic activities when exposed to GBMs.